2016
DOI: 10.1111/jsbm.12268
|View full text |Cite
|
Sign up to set email alerts
|

Pay-for-Performance, Employee Participation, and SME Performance

Abstract: This study examines how pay‐for‐performance (PFP) systems affect the performance of small‐ and medium‐sized enterprises (SMEs). We decompose PFP into two dimensions: scope and depth. PFP scope captures the variety of performance measures and reward types included in a firm's PFP system, and PFP depth reflects the relative amount of performance‐based pay compared with total pay. We posit that PFP scope has a positive whereas PFP depth has an inverted U‐shaped effect on employee participation, which in turn enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 75 publications
(130 reference statements)
0
36
0
Order By: Relevance
“…The first one discloses perspectives of soft and hard remuneration goals. Some authors such as Wang, Thornhill and Zhao (2016) executed research in a pay for performance study covering outcome evaluations assessment and employee participation. It disclosed a trend that systems focused on hard remuneration goals are more applicable as opposed to soft goals.…”
Section: Characteristics Of Remuneration Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one discloses perspectives of soft and hard remuneration goals. Some authors such as Wang, Thornhill and Zhao (2016) executed research in a pay for performance study covering outcome evaluations assessment and employee participation. It disclosed a trend that systems focused on hard remuneration goals are more applicable as opposed to soft goals.…”
Section: Characteristics Of Remuneration Systemsmentioning
confidence: 99%
“…Still, there is insufficient knowledge regarding the complex approach on the characteristics that identify remuneration systems. Some possible approaches could be found in Armstrong (2009), Armstrong and Murlis (2007), Wang, Thornhill, Zhao (2016), Milkovich, Newman, Gerhart (2014, Martocchio (2013), Biswas (2013), Costa, Passos, Bakker (2014) and other works. It should be noted that so far, not only in Lithuania but also worldwide, there is a lack of systematic research focused on the expression of the characteristics of remuneration systems in the context of sustainable human resource management.…”
Section: Introductionmentioning
confidence: 99%
“…Employee involvement is an antecedent of engagement (Saks & Rotman, 2006). It is defined as the inclusion of employees into the organisation's decision-making process or the implementation of new strategies that affect the employees' work (Rees & French, 2010;Wang, Thornhill, & Zhao, 2016). A survey conducted by Truss et al (2006) suggested that establishing employee involvement makes a difference to organisational performance.…”
Section: Rewards According Tomentioning
confidence: 99%
“…HRM and organizational psychology literature suggest the existence of extensive studies to explore the impact of employee participation on numerous constructs. For instance, employee participation and job satisfaction, employee commitment and employee productivity (Bhatti & Qureshi, 2007;Miller & Monge, 1986;Zhu, et al, 2015;Tafvelin, von Thiele Schwarz, Nielsen & Hasson, 2019;Basterretxea & Storey, 2018;Rogiest, Segers & van Witteloostuijn, 2018;Noe, Hollenbeck, Gerhart & Wright, 2017;Glavas, 2016), organizational performance (Summers & Hyman, 2005;Wang, Thornhill & Zhao, 2018), industrial democracy (Poole, 2017;Rasmussen, 2009), and PAs (Cawley, et al, 1998;Roberts, 2003;Thomas & Bretz Jr, 1994;Babagana, Mat & Ibrahim, 2019a & b;Rubin & Edwards, 2018;Islami, Mulolli & Mustafa, 2018;Babagana, Mat & Ibrahim, 2018;Rukumba & Iravo, 2019).…”
Section: Employee Participationmentioning
confidence: 99%